Aplicação de 5-bromo-1,1,1-trifluor-4-metoxipent-3-en-2-ona na síntese de pirróis, pirazóis, pirimidinas e 1,2,3-triazóis - Aquino, Estefania da Costa (2015)
This thesis reports the synthesis of various series of trifluoromethyl substituted nitrogenated heterocycles, such as pyrroles, pyrazoles, pyrimidines and 1,2,3-triazoles, exploiting the synthetic versatility of 5-bromo-1,1,1-trifluoro-4-methoxypent-3-en-2-one in reactions with nitrogenated nucleophiles. In this way, synthesis of a novel series of 4-amino-3-trifluoromethyl-1H-N-substituted pyrroles was performed through two reaction steps. In the first stage is an addition reaction of primary or secondary amine in the 4-position of 5-bromo-1,1,1-trifluoro-4-methoxy-3-penten-2-one furnishing 4-amino-5-bromo-1,1,1-trifluoropent-3-en-2-one. The second stage is a nucleophilic substitution of the bromine by a primary amine followed by an intramolecular cyclocondensation reaction resulting in the formation of pyrroles with yields from 50 to 98%. Through the reaction of 5-bromo-1,1,1-trifluoro-4-methoxypent-3-en-2-one with sodium azide, 5-azido-1,1,1-trifluoro-4-methoxypent-3-en-2-one was obtained. This compound was subjected to cycloaddition reaction [3 + 2] with terminal alkynes, allowing the synthesis of a novel series of 1,1,1-trifluoro-4-methoxy-5-(4-alkyl/aryl-1H-1,2,3-triazol-1-yl)-pent-3-en-2-one (I) in good yields (74-90%). Through this reaction a wide range of bi-heterocycle compounds was obtained. For example, the reaction of compound I with 2-methylisothiourea sulfate gave a series of 4-(1H-1,2,3-triazol-1-yl)-methyl-6-trifluoromethyl pyrimidine (72-79%). In a second step, the SCH3 group of these pyrimidines was oxidized to SO2CH3 and subsequently substituted by primary and secondary amines to give a series of 2-aminopyrimidines derivatives in yields of 70-93%. Furthermore, the reaction with N1-substituted 2-methylisothiourea sulphates furnished two products: a 4-pyrimidinone and 1,4-dihydropyrimidine derivatives, depending on the reaction conditions employed. From the reaction of compound I with hydrazines and hydrazides a series of 4-[(4-alkyl/aryl-1H-1,2,3-triazol-1-yl)methyl]-5-hydroxy-5-trifluoromethyl-4,5-dihydro-1H-pyrazole, in yields of 77-90%, was obtained. The products obtained in this study were characterized by 1H- and 13C- NMR, mass spectrometry, high resolution mass spectrometry, elemental analysis, and X-ray diffraction. Keywords: 5-bromo-1,1,1-trifluoro-4-methoxypent-3-en-2-one, 5-bromo-4-enaminoketone, 4-amino-3-trifluoromethyl-1H-pyrroles N-substituted, 1,2,3-triazole, pyrimidine, pyrazolines, bi-heterocycles.